Stanislavski : an introduction - Benedetti, Jean (Methuen Drama, 2000)
The Stanislavski 'system' is still the only comprehensive method of actor training we possess. This text shows the slow growth of the 'system', from its roots in the tradition of Russian realism, and charts the various phases it went through until the final emergence of the Method of Physical Action in the years before his death.